Denmark : Financial Sector Assessment Program, Macroprudential Policies: Technical Note. (IMF Staff Country Reports; Country Report ;, 2014)
This technical note discusses significance of macroprudential policies for Denmark. Macroprudential policy seeks to contain the buildup of macrofinancial imbalances associated with credit booms and asset price bubbles, a function which is particularly important in Denmark, where the space for monetary policy action is limited. This note provides an analysis of existing frameworks used in Denmark for identifying systemic risk of both structural and cyclical nature. The note also suggests additional tools that the authorities could use to further enhance their capacity to evaluate systemic risks.